Le parcours tumultueux des propos injurieux en droit québécois depuis 2009 : l’arrêt Génex Communications inc. c. Association québécoise de l’industrie du disque, du spectacle et de la vidéo (ADISQ) est-il toujours pertinent ? - Grégoire, Marie (Les Cahiers de droit, 2016)
This text compares the position adopted by the Court of Appeal in 2009 on the punishment of insults in the Genex ruling with the decisions rendered since then by the Supreme Court of Canada and the Quebec Court of Appeal. This analysis shows that the positions of the courts have changed and that offensive and insulting comments can no longer be sanctioned independently, as they were in Genex. The outcome is that insults must qualify as a breach of the right to the safeguard of reputation or of the right to equality, without which it will be found that the damage to the safeguard of dignity resulting from the insults cannot be considered as giving rise to compensation. The new analytical framework generates a confused amalgam in the distinction of rights guaranteed by the Charter of Human Rights and Freedoms.